The impact of the New York City marathon on hotel demand - Joshua Martin; Joshua C. Hall (Economies, 2020)
Daily hotel data are employed, along with information on prices, revenue, demand and hotel occupancy, to analyze part of the local economic impact of the annual New York City (NYC) Marathon. As the largest competitive race in the world, the marathon attracts domestic and international competitors and spectators. The cancellation of the 2012 marathon due to Hurricane Sandy was estimated to lead to an increase of 4000 hotel nights as well as a 10% increase in the average daily room rate. Taken together, this is associated with a USD 3 million increase in hotel revenue. The results suggest a significantly lower local economic impact of the race than previously thought.
Keywords: Z20; Z32; 330; economic impact; hotel demand; hotel revenue; running